ECCO2R as a bridge to a decision in type II respiratory failure - Grauslytė, Lina; De La Cerda, Gonzalo; Jovaiša, Tomas (Acta medica Lituanica, 2019)
Introduction. End-of-life decisions are often time consuming and difficult for everyone involved. In some of these cases extracorporeal life support systems could potentially be used not only as a bridge to treatment but as a tool to buy time to allow patient’s participation in decision making and to avoid further futile invasive procedures. Case report. A previously healthy 53-year-old female patient presented with respiratory failure of unknown cause. In the course of treatment her condition was deemed irreversible and the only option for any chance of long-term survival was a lung transplant. During this whole time the patient’s condition was managed with extracorporeal carbon dioxide removal system (ECCO2R). She remained compos mentis and expressed the wish to stop all the treatment as the option of lung transplant was not acceptable to her. Treatment was withdrawn and she passed away. Discussion. In cases of end-of-life decisions, time can play an essential role. Even though extracorporeal life support systems have been conceptualised to be a bridge to treatment, they could be beneficial in a situation when time is needed to make a decision. ECCO2R has been used as a treatment method in different settings, however, in this case it served as a tool to maintain the patient alive and conscious for a sufficient time for her to participate in decision making. Conclusions. Our case report demonstrated that ECCO2R could serve as a bridge to decision in situations when time is limited and the decisions that need to be made are difficult.